Perception and Preferences of E-resources among Faculty Members of National Institute of Technology (NIT) Kurukshetra - Sharma, Chetan; Sharma, Ritu (Journal of Information and Knowledge, 2010)
E-resources are the essential part of any university and research library in the era of e-learning. E-resources are the latest means of teaching, learning and sharing. Present paper examines the use and impact of various e-resources among the faculty members of NIT Kurukshetra.